2022
DOI: 10.1177/23969873211062011
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in incidence of oral anticoagulant-related intracerebral hemorrhage over the past decade in the Netherlands

Abstract: Background Data on oral anticoagulant-related (OAC) intracerebral hemorrhage (ICH) incidence are scarce. Most studies on incidence time trends were performed before the introduction of Direct Oral Anticoagulants (DOACs). Between 2008 and 2018, the number of OAC-users in the Netherlands increased by 63%, with the number of DOAC-users almost equaling that of Vitamin K Antagonists (VKA)-users. We aimed to determine the recent total and OAC-related ICH incidence and assess changes over the last decade, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
(71 reference statements)
0
7
1
Order By: Relevance
“…For example, a meta-analysis by Li et al [8] from 2022 found no significant temporal trend in ICH incidence between 1996 and 2017 in high-and upper middle-income countries. A regional population-based study on OAC ICH incidence from the Netherlands showed a significant decline in OAC ICH incidence despite an increased number of OAC users between 2007-2009 and 2017-2019 [17], whereas our data showed a 56% increase in OAC ICH incidence. However, the initial proportion of OAC ICH in the Dutch study was with 25.8% almost twice as high compared to our results (13.1% 2010-2012 in Sweden) which might explain the opposite trend in OAC ICH incidence.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…For example, a meta-analysis by Li et al [8] from 2022 found no significant temporal trend in ICH incidence between 1996 and 2017 in high-and upper middle-income countries. A regional population-based study on OAC ICH incidence from the Netherlands showed a significant decline in OAC ICH incidence despite an increased number of OAC users between 2007-2009 and 2017-2019 [17], whereas our data showed a 56% increase in OAC ICH incidence. However, the initial proportion of OAC ICH in the Dutch study was with 25.8% almost twice as high compared to our results (13.1% 2010-2012 in Sweden) which might explain the opposite trend in OAC ICH incidence.…”
Section: Discussioncontrasting
confidence: 89%
“…At the same time the proportion of especially older AF-patients treated with OAC has increased [14], not least because of the introduction of non-vitamin K oral anticoagulants (NOACs) which are associated with a lower risk for ICH compared to treatment with vitamin K antagonists (VKA) [15]. All these factors might influence trends in ICH incidence, but recent studies have shown diverging results, also in OAC-associated ICH incidence [16, 17]. The aim of this register-based, nationwide study was to analyze trends in first-ever ICH incidence in Sweden between 2010 and 2019 with focus on non-OAC and OAC-associated ICH.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of ICH with prior OAC use (OAC-ICH) increased from 0.8 per 100,000 in 1988 to 4.4 per 100,000 in 1999, before DOACs became available in the United States 18 . However, two recent studies from Denmark and the Netherlands showed that the incidence of OAC-ICH was decreasing from before and after DOACs became available (33 or 10.5 per 100,000 person-years to 24 or 7.7 per 100,000 person-years, respectively) 29 , 30 . These findings may reflect DOACs having about a 50% lower risk of intracranial bleeding compared to warfarin in patients with AF 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, in South Limburg, in the Netherlands ( 68 ), in the period between 2007 and 2009, 25.8% of total ICH (168 of 652) have been associated with OACs use in patients on VKA. An annual incidence of 40.9 total ICH and 10.5 OAC-related ICH per 100,000 people has been reported.…”
Section: Discussionmentioning
confidence: 99%